Integrated Digital Transformation System Model for Technology, Process, and Capability Alignment - Rakesh Pradhan (Techne: Journal of Engineering, Technology and Industrial Applications, 2026)
Digital transformation has become a strategic engineering and organizational challenge because technology adoption alone rarely produces sustainable performance improvement. Organizations need an integrated system model that aligns digital technologies, business processes, and organizational capabilities. This study designed a Digital Transformation System Model that explains how technology architecture, process redesign, and organizational capability development can be integrated into a coherent transformation system. A structured literature review was conducted using 42 peer-reviewed and high-relevance academic sources published between 2013 and 2025. The review followed identification, screening, eligibility, coding, synthesis, and model-building stages. Thematic coding was applied to classify transformation components into technology, process, capability, governance, value creation, and feedback mechanisms. The review identified three dominant transformation layers: digital technology infrastructure, business process reconfiguration, and organizational capability orchestration. Technology-related constructs appeared in 83.33% of reviewed studies, process-related constructs in 66.67%, and capability-related constructs in 78.57%. The proposed model links digital infrastructure, data integration, process modularity, agile governance, workforce capability, analytics capability, and performance feedback into a closed-loop transformation system. Digital transformation should be designed as a socio-technical system rather than as isolated technology implementation. The proposed model offers a structured framework for organizations seeking to align digital investments with process performance, capability maturity, and measurable transformation outcomes.